Exploring stakeholders perspectives on TB contact investigation in Cali, Colombia: a qualitative study - Jairo E. Palomares Velosa; Jairo E. Palomares Velosa; Jorge E. Figueroa Gómez; Claudia N. Rojas Zúñiga; Gustavo Díaz; Gustavo Díaz; Beatriz E. Ferro; J. Lucian Davis; J. Lucian Davis; Lauretta E. Grau (Frontiers Media S.A., 2023)
IntroductionContact investigation is a proven intervention for tuberculosis (TB) case finding and prevention. Although widely endorsed by national public health authorities and the World Health Organization, many countries struggle to implement it effectively. The objective of the study is to describe and characterize the barriers and facilitators of TB contact investigation in Cali, Colombia from the perspective and experience of the key stakeholders involved.MethodsWe collected data from group discussions during two workshop sessions with clinic and public health staff involved in TB contact investigation (June 2019 and March 2020 respectively) and semi-structured interviews with TB cases and their household contacts (July 2019 to April 2020). We undertook an inductive thematic analysis with the RADaR technique to characterize the barriers and facilitators of the TB contact investigation process.ResultsThe two workshops included 21 clinics and 12 public health staff. We also conducted 26 semi-structured interviews with TB cases and their household contacts. Using thematic analysis, we identified four common themes: Healthcare Operations, Essential Knowledge, Time Limitations and Competing Responsibilities, and Interpersonal Interactions. The main barriers to conducting household visits were low data quality, stigma and mistrust, safety concerns for health workers, and limited resources. The main barriers to TB uptake by contacts were competing responsibilities, low TB risk perceptions among contacts, and difficulty accessing diagnostic tests for contacts. In contrast, good communication and social skills among health workers and accurate TB knowledge facilitated successful household visits and TB test uptake, according to key stakeholders.ConclusionThis study provides a deeper understanding of TB contact investigation barriers and facilitators in a high-prevalence urban setting in a middle-income country from the perspective and experience of key stakeholders. The study shed light on the barriers that hinder household contacts engagement and TB test uptake such as issues of systemic capacity and TB knowledge. Also, highlighted facilitators such as the importance of interpersonal communication skills among health workers in the public and private sector. The insights from this study can serve as a valuable resource for public health organizations seeking to enhance their contact investigation efforts and improve TB control in similar settings.